The Phenomenon of Ngobrok (Palm Oil Fruit Theft) Case Study: Sibak Village Community, Ipuh District, Mukomuko - Puspita Sari Manik, Desy; Wardaya, Sulistya; Widiyarti, Diyas (Dinasti Research, 2025)
This study describes the findings of researchers that underlie the occurrence of the Ngobrok phenomenon in Sibak Village, most of whose land has been controlled by companies. Palm oil fruit theft often occurs due to limited access to productive land, low levels of community education, and urgent economic needs. The method used in this study is a qualitative approach with in-depth interview techniques. Data obtained from perpetrators and farmers were analyzed using the conflict theory proposed by Karl Max. This theory is used to understand the social and economic inequality that underlies the act of theft, where people who lose access to land become marginalized groups and are forced to take illegal actions to meet their living needs. The results of this study indicate that the dominance of companies in controlling land, low levels of community education, and limited employment opportunities are the main factors that trigger Ngobrok or palm oil fruit theft.